Selected Logistics Development Level Indicators0.25em- a Review and Comparative Analysis in European Union Countries - Joanna Górniak (Comparative Economic Research. Central and Eastern Europe, 2022)
The logistics industry today is well developed. The efficient movement of goods, people, and information is a crucial link in each supply chain and the entire logistics system. For systems to function effectively, they must be properly assessed, compared, and analyzed. Therefore, there are many different indicators, both simple and complex. The purpose of this article is to review these indicators and conduct a comparative analysis for a selected indicator, the LPI (Logistics Performance Index), which measures logistics performance. The subjects of the study are European Union countries. Multivariate comparative analysis was used for the study
Keywords: L91; M20; O18; 330; logistics system; logistic indicators; Logistics Performance Index; multivariate comparative analysis